The Verbier Festival celebrates its 25th anniversary (II/II) Verbier Festival 2018 - Bach, Johann Sebastian 1685-1750; Sarasate, Pablo de 1844-1908; Heidrich, Peter 1935-; Mozart, Wolfgang Amadeus 1756-1791; Handel, George Frideric 1685-1759; Strauss, Johann 1825-1899; Strauss, Johann 1825-1899 (Idéale Audience with the participation of medici.tv, 2018)
In the summer of 2018, the Verbier Festival celebrated its first quarter of a century, inviting some of the world's greatest string players to an exceptional gala concert! Violinists, violists, and cellists of all ages were brought together on one stage to perform works by Bach, Sarasate, Mozart, Handel, and Strauss II, not to mention a very special version of "Happy Birthday.
Keywords: Concert films; Internet videos